Bounding Attachment dan Postpartum Blues Pada Pasien Pasca Operasi Sectio Caesarea - Anita Anita; Anggita Febriany; El Rahmayati (Malahayati Nursing Journal, 2024)
ABSTRACT The prevalence of postpartum blues is 3-8% with 50% occurring in the productive age group 20-50 years. Postpartum blues cases are 26-85% in Asia, in Indonesia it will be 70-80% in 2020. Objective: to determine the relationship between bounding attachment and the incidence of postpartum blues in patients after caesarean section surgery at RSIA AMC Metro City. Method: Quantitative research type, cross sectional method. Sample of 75 respondents, purposive sampling technique, data collection tool, Edinburgh Postnatal Depression Scale questionnaire bounding attachment observation. Chi Square test analysis. Results: Post partum mothers who did not do good bonding attachment experienced post partum blues as many as 37 (88.1%), mothers who did good bonding attachment experienced postpartum blues as many as 3 respondents (9.1%).  The results of the chi square test obtained a p-value = 0.000, so it was found that bounding attachment had a significant relationship with the incidence of postpartum blues in patients after caesarean section surgery. OR = 74,000, meaning that mothers who are not good at bonding attachment have a 74 has risk of experiencing postpartum blues. Conclusion: There is a relationship between postpartum SC mother's bounding attachment and the occurrence of postpartum blues. Post partum SC mothers are expected to strengthen their affection by increasing interactions with their babies such as Direct Breastfeeding, touch, eye contact and active communication with their babies. Keywords: Sectio Caesarea, Postpartum Blues, Bounding Attachment  ABSTRAK Prevalensi postpartum blues 3-8% dengan 50% terjadi pada usia produktif 20-50 tahun (WHO, 2021). Kasus postpartum blues 26-85% di Asia, di Indonesia menjadi 70-80% tahun 2020 (Annisa, 2022). Tujuan: untuk mengetahui hubungan bounding attachment dengan kejadian posartum blues pada pasien pasca operasi sectio caesarea di RSIA AMC Kota Metro. Metode: Jenis penelitian kuantitaif, metode cross sectional. Sampel 75 responden, teknik purposive sampling, Alat pengumpulan data kuesioner Edinburg Postnatal Depression Scale observasi bounding attachment. analisis uji Chi Square. Hasil:  Ibu post partum yang tidak baik melakukan bounding attachment mengalami post partum blues sebanyak 37 (88,1%), Ibu yang melakukan bounding attachment yang baik mengalami postpartum blues sebanyak 3 responden (9,1%) .  Hasil uji chi square diperoleh nilai p-value = 0,000, sehingga didapat bounding attachment memiliki hubungan signifikan terhadap kejadian postpartum blues pada pasien pasca operasi sectio caesarea. OR = 74.000, artinya Ibu yang tidak baik melakukan bounding attachment berisiko 74 kali mengalami postpartum blues Kesimpulan: Terdapat hubungan antara bounding attachment ibu post partum SC dengan terjadinya post partum blues. Ibu Post partum SC diharapkan mempererat kasih sayang dengan memperbanyak interaksi dengan bayi seperti Direct Breastfeeding, sentuhan, kontak mata dan berkomunikasi aktif kepada bayinya. Kata Kunci: Sectio Caesarea, Postpartum Blues, Bounding Attachment